Challenges and Government Initiatives in the MSME Sector: A Study on Awareness and Issues Faced by Entrepreneurs in Haryana (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
The Micro, Small and Medium Enterprises (MSME) sector plays a pivotal role in Haryana's economic development, contributing significantly to GDP, industrial output and exports. This study explores the effectiveness of government initiatives aimed at promoting the MSME sector in Haryana, with a particular focus on the level of awareness among entrepreneurs and the challenges they face. Despite the existence of several supportive policies and programs, the study finds that awareness levels among MSME entrepreneurs, particularly in rural areas, remain low, hindering the successful implementation of these initiatives. Key challenges identified include limited access to finance, outdated technology, inadequate infrastructure and stiff competition from multinational corporations. The study suggests that targeted efforts, including improved dissemination of information, the use of social media and specialized support for rural and female entrepreneurs, are essential to enhance the sector's growth and sustainability. A robust policy framework that addresses these challenges can significantly bolster the MSME sector’s contribution to the state's economic development.